Organizational Culture Shapes the Adoption and Incorporation of Simulation into Nursing Curricula: A Grounded Theory Study - Karyn Taplay; Susan M. Jack; Pamela Baxter; Kevin Eva; Lynn Martin (Nursing Research and Practice, 2014)
Purpose. To create a substantive mid-range theory explaining how the organizational cultures of undergraduate nursing programs shape the adoption and incorporation of mid-to high-level technical fidelity simulators as a teaching strategy within curricula. Method. A constructivist grounded theory was used to guide this study which was conducted in Ontario, Canada, during 2011-12. Semistructured interviews (n=43) with participants that included nursing administrators, nursing faculty, and simulation leaders across multiple programs (n=13) informed this study. Additionally, key documents (n=67) were reviewed. Purposeful and theoretical sampling was used and data were collected and analyzed simultaneously. Data were compared among and between sites. Findings. The organizational elements that shape simulation in nursing (OESSN) model depicts five key organizational factors at the nursing program level that shaped the adoption and incorporation of simulation: (1) leaders working in tandem, (2) information exchange, (3) physical locale, (4) shared motivators, and (5) scaffolding to manage change. Conclusions. The OESSN model provides an explanation of the organizational factors that contributed to the adoption and incorporation of simulation into nursing curricula. Nursing programs that use the OESSN model may experience a more rapid or broad uptake of simulation when organizational factors that impact adoption and incorporation are considered and planned for.